Family Relationships in an Aging Society - Martie Gillen; Terry Mills; Jenny Jump (EDIS)
Never in the history of America or the world has the population had more older adults than children. This revised 5-page fact sheet discusses some issues that happen as a result of having a greater number of older adults than children. It also looks at the roles of the family and intergenerational relationships supporting our aging society. Written by Martie Gillen, Terry Mills, and Jenny Jump, and published by the UF Department of Family, Youth and Community Sciences, November 2012.